1982
DOI: 10.1177/0148607182006005395
|View full text |Cite
|
Sign up to set email alerts
|

Serum Protein Response to Surgery and Starvation

Abstract: To investigate the effect of stress on the dynamics of serum protein response during starvation, serum albumin, prealbumin, and transferrin changes were studied in six chair-adapted macaques during two separate 7-day test periods: (1) Starvation--NPO + IV D5/W (100 cc/kg/day), and (2) Surgery/starvation--laparotomy and gastrostomy + NPO + IV D5/W (100 cc/kg/day). During the starvation period, transferrin was the only protein that decreased from baseline values and did so at day 7 of the study period. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…APR to tissue trauma (Kushner, 1982) is related to the insult type and its magnitude (Fouad et al, 1992;McCracken et al, 1984). In humans, alterations of plasma APR levels are an important response to starvation (Smale et al, 1982), infection (Evans et al, 1980), or surgical injury (Aronsen et al, 1972;Colley et al, 1983). A multiple APR has been observed after acute myocardial infarction (Kushner et al, 1978), surgical injury (Voulgari et al, 1982), severe head injury (Ferard et al, 1981), and with the development of sepsis (Witte et al, 1982).…”
mentioning
confidence: 99%
“…APR to tissue trauma (Kushner, 1982) is related to the insult type and its magnitude (Fouad et al, 1992;McCracken et al, 1984). In humans, alterations of plasma APR levels are an important response to starvation (Smale et al, 1982), infection (Evans et al, 1980), or surgical injury (Aronsen et al, 1972;Colley et al, 1983). A multiple APR has been observed after acute myocardial infarction (Kushner et al, 1978), surgical injury (Voulgari et al, 1982), severe head injury (Ferard et al, 1981), and with the development of sepsis (Witte et al, 1982).…”
mentioning
confidence: 99%
“…The lack of PTH response indicates that calcium in conjunction with other factors may blunt the normal PTH response. Calcium is a known regulator of 1‐alpha hydroxylase activity and PTH secretion . Albumin corrected calcium increased significantly after surgery and could theoretically augment the observed 35% decrease in serum 1,25(OH) 2 D 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Injury or trauma induces a series of metabolic, inflammatory, and endocrine changes known as the “surgical stress response.” A particular and abrupt event in response to surgery is a profound change in the distribution of proteins between the intra‐ and extravascular compartments . This redistribution gives rise to an instant reduction in the concentration of most circulating proteins, which necessitates immediate changes in factors dependent on protein binding in serum, for instance, calcium and steroid hormones …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Smale et al 25 ) have reported that the TTR level in macaques was not altered by 7 days of starvation, and that the addition of surgical stress significantly decreased the TTR level. The cause of the difference in TTR response to starvation and surgical stress between the rat and macaque is not clear.…”
Section: Effect Of the Acute-phase Response On Plasma Rapid-turnovermentioning
confidence: 99%